2003
DOI: 10.1063/1.1610798
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic photonic band-gap material at microwave frequencies based on ferromagnetic nanowires

Abstract: We present an experimental investigation of a class of microwave photonic band-gap (PBG) materials, in which the magnetic permeability μ varies periodically within the material. This material is fabricated using a periodic arrangement of arrays of magnetic nanowires. As for dielectric or metallic PBG, the band-gap behavior varies with the geometrical parameters fixing the spatial periodicity of the magnetic structure. The magnetic photonic band gap is induced by the presence of a ferromagnetic resonance effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 12 publications
1
50
0
Order By: Relevance
“…It is fast and thereby suitable for scaling-up to produce large numbers of devices. For example, arrays of cylindrical magnetic nanowires deposited electrochemically within porous membranes 142,143,144 have attracted much attention due to their potential for use as microwave 145 and THz 13 devices.…”
Section: µMmentioning
confidence: 99%
“…It is fast and thereby suitable for scaling-up to produce large numbers of devices. For example, arrays of cylindrical magnetic nanowires deposited electrochemically within porous membranes 142,143,144 have attracted much attention due to their potential for use as microwave 145 and THz 13 devices.…”
Section: µMmentioning
confidence: 99%
“…As shown in this figure, we have a band-pass filter with low full width at half maximum as compared with other NW-based filters [10]. In addition, other NW-based magnetic photonic crystals must be prepared by electron beam lithography which is expensive as compared with our proposed structure.…”
Section: Resultsmentioning
confidence: 93%
“…Until now, magnetic materials, which have a relative permeability different from unity in the microwave region, can be exploited for microwave filters in the magnetic photonic band gap (magnetic photonic crystal (MPC)) construction. Widespread MPC-based microwave filters consist of an array of parallel ferromagnetic nanowires electrodeposited into a porous polycarbonate membrane [7][8][9][10]. These structures display the photonic band gap effect attended by the ferromagnetic resonance (FMR) in the vicinity of the band gap frequency.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that under specific conditions, especially porosity and filling height of wires, a tunable magnetodielectric effect can be obtained. Furthermore a proper choice of the porosity should enable to create double negative substrates (ε and µ negative) enabling left-handed propagation for miniaturized Magnetic/Dielectric Electromagnetic Bandgap structures based on periodic substrates [3], [7].…”
Section: Resultsmentioning
confidence: 99%